Cross-talk and regulation between glutamate and GABAB receptors - Kantamneni, Sriharsha (Frontiers in Cellular Neuroscience, 2015)
Brain function depends on co-ordinated transmission of signals from both excitatory and inhibitory neurotransmitters acting upon target neurons. NMDA, AMPA and mGluR receptors are the major subclasses of glutamate receptors that are involved in excitatory transmission at synapses, mechanisms of activity dependent synaptic plasticity, brain development and many neurological diseases. In addition to canonical role of regulating presynaptic release and activating postsynaptic potassium channels, GABAB receptors also regulate glutamate receptors. There is increasing evidence that metabotropic GABAB receptors are now known to play an important role in modulating the excitability of circuits throughout the brain by directly influencing different types of postsynaptic glutamate receptors. Specifically, GABAB receptors affect the expression, activity and signalling of glutamate receptors under physiological and pathological conditions. Conversely, NMDA receptor activity differentially regulates GABAB receptor subunit expression, signalling and function. In this review I will describe how GABAB receptor activity influence glutamate receptor function and vice versa. Such a modulation has widespread implications for the control of neurotransmission, calcium-dependent neuronal function, pain pathways and in various psychiatric and neurodegenerative diseases.